Examining suicide risk among people with schizophrenia, focusing on the role of anosognosia and the ethical considerations for future research directions - Kotzé, Carla; Roos, Johannes Lodewikus (Frontiers in Psychiatry, 2025)
This perspective paper discusses the primary risk factors consistently identified in systematic reviews of suicide among individuals with schizophrenia. Particular attention is given to the intricate relationship between anosognosia (lack of insight into one’s illness) and suicide risk in this population. This paper explores how anosognosia may influence other established risk factors and potentially contribute to suicidal behavior in patients with schizophrenia. By analyzing this complex interplay, this paper aims to provide a more comprehensive understanding of suicide risk in schizophrenia, potentially informing more effective prevention strategies and interventions for this vulnerable group. Future research in this area should carefully consider the ethical implications, including the potential impact of interventions on individuals with varying levels of insight into their condition. Researchers must prioritize participant safety and well-being while balancing the need to advance knowledge in this critical field.